IMPLEMENTATION OF RELIABILITY CENTERED MAINTENANCE (RCM) II IN PACKAGING INDUSTRY PRODUCTION MACHINERY MAINTENANCE ACTIVITIES: Implementasi Reliability Centered Maintenance (RCM) II Pada Aktivitas Perawatan Mesin Produksi Industri Packaging - Wahyu Nugroho; Tedjo Sukmono (Journal for Technology and Science, 2024)
Along with the increasing need for productivity and the use of high technology in the form of production machines and factories, the need for maintenance functions is also increasing. At PT. Weiss Tech, a packaging machine manufacturer, has problems mainly related to wire cut machine malfunctions which cause interruptions and delays in the production process and reduce machine performance. In overcoming these problems in this study, the Reliability Centered Maintenance (RCM) II method from Failure Modes and Effect Analyze (FMEA) was used. RCM II is one of the methods used to determine which components are due for repairs, while FMEA is defined as a method for identifying the root cause of engine failure. From the results of calculations using FMEA and RCM II, the results of the maintenance interval for the Electromotor component (electric motor) with a maintenance interval of 20 hours, for the Lower and upper nozzle components (upper and lower nozzles) with a maintenance interval of 181 hours, and for the Roller component (drive roller) ) with a treatment interval of 177 hours